Cortical inhibition, pH and cell excitability in epilepsy: what are optimal targets for antiepileptic interventions?. (21st November 2012) - Pavlov, Ivan; Kaila, Kai; Kullmann, Dimitri M.; Miles, Richard
Abstract : Abstract  Epilepsy is characterised by the propensity of the brain to generate spontaneous recurrent bursts of excessive neuronal activity, seizures. GABA‐mediated inhibition is critical for restraining neuronal excitation in the brain, and therefore potentiation of GABAergic neurotransmission is commonly used to prevent seizures. However, data obtained in animal models of epilepsy and from human epileptic tissue suggest that GABA‐mediated signalling contributes to interictal and ictal activity. Prolonged activation of GABAA receptors during epileptiform bursts may even initiate a shift in GABAergic neurotransmission from inhibitory to excitatory and so have a proconvulsant action. Direct targeting of the membrane mechanisms that reduce spiking in glutamatergic neurons may better control neuronal excitability in epileptic tissue. Manipulation of brain pH may be a promising approach and recent advances in gene therapy and optogenetics seem likely to provide further routes to effective therapeutic intervention.